(Syntesis of rose oil from the terpeneles java citronella oil) - Salya Sait; Enny Hawani Lubis (Warta Industri Hasil Pertanian, 1995)
In order to diversify the end-use and raise the commercial value of java citronella oil,two G-types of the oil obtained from the steam distillation of G-3 and G-mixture of the Mahapengiri (Cymbopogon winterianus Jowitt)leaves, were deterpenated by the method of selective extration of the soluble oxygebated constituents in dilute alcohol as well as the method of chromatography using alumina as the absorbant,nonpolar ofganic (hexane)and polar one (ethyl acetate).To complete the preparation of the basic material for the synthesis of rose oil,the terpeneles products were then mixed with the calculated volumes of phenethyl alcohol comparable to that of the Turkish rose oil,instead to that of the commercial Bulgarian which had been analyzed in the experimental.The result of the experiments concluded that the terpeneless oils obtained from the deterpenation method of selective extration were the most favourable for the preparation of the basic material for the synthesis of rose oil,since the ratios of the citronella/geraniol contents were between one and two respectively.